Мастер и Маргарита: [роман] / Михаил Булгаков - Булгаков Михаил Афанасьевич (Лучшая мировая классика, 2021)
Экземпляры: Ф-18 (20220304) / Инвентарный номер: 97229 / Цена: / Сис.шифр: 84(2=411.2)6-4 / Авт.знак: Б 90 / ББК: 84(2=411.2)6-4